Challenge in Diagnosing and Managing Carotid Caverous Fistula in Patient with Intermittent Angle Closure Glaucoma - Maria Magdalena; Virna Dwi Oktariana; M Sidik (Majalah Oftalmologi Indonesia, 2016)
Background: The purpose of this case report is to present a patient with Carotid Cavernous Fistula (CCF) superimposed angle closure glaucoma and how to manage the IOP and to describe treatment options for CCF. Case Report: A 72-year old female patient was consulted to Glaucoma Division with chief complain the redness of the right eye (RE). She also had blurred vision on both eyes and high IOP of the RE. The IOP of the RE tend to be fluctuated even after laser peripheral iridotomy (LPI) from prior hospital, and was different from the LE, which was stable on anti-glaucoma medication. A careful history taking, clinical examination including visual acuity and visual field defect test, and also ancillary test to confirm the diagnosis were done. The patient was assessed with intermittent angle closure glaucoma (ACG) of both eyes superimposed with carotid-cavernous fistula (CCF) of the RE and planned to undergo trabeculectomy and phacoemulsification surgery from glaucoma division, and also embolization procedure from neuro ophthalmology division. However, the schedule of embolization will be done one year later due to long waiting list at Radiology Departement.Conclusion: This case demonstrates CCF of the RE superimposed intermittent ACG of both eyes. The Clinical manifestation of CCF were subtle, therefore clinical examination and acillary test such as CT angiography were needed to establish the diagnosis and to exclude differential diagnosis. The definitive therapy for CCF is to closure the fistula, but due to long waiting list we have to consider carotid massage as conservative management. In this case carotid massage gave good result in reducing ocular manifestation of CCF. Â Keyword: Carotid Cavernous Fistula, Glaucoma, Angle-closure Glaucoma, Carotid Massage